Recent upgrades to the calibration system of the CMS HCAL - Thayil Steffie Ann; Martinez German (EPJ Web of Conferences)
The irradiation of the CMS Hadron Calorimeter (HCAL) subdetectors results in decreased signal output from the active materials as well as increased noise in the photodetectors used to read out the system. The HCAL has a dedicated calibration system used to monitor and correct for these effects and to help synchronise the timing of the subdetectors. The calibration system is described with a focus on the upgrades to the laser system, which has undergone significant changes since the end of Run 2 of the LHC in 2018. A new solid state laser has been installed and commissioned, and the optical setup for light distribution has been simplified. An upgrade to the laser trigger board has reduced the laser trigger jitter by an order of magnitude. A new system has also been developed to fire the laser, based on existing HCAL electronics. Future improvements to the system are also presented, including ongoing work on extending the system to include remote monitoring capabilities.